The Relationship Between Organizational Safety Culture and Organization Safety Performance. The Mediating Role of Safety Management System - Otitolaiye, Victor Olabode; Abd Aziz, Fadzli Shah; Munauwar, Munawar; Omer, Faris (International Journal of Occupational Safety and Health, 2021)
Introduction: Safety performance is defined as efforts undertaken by organizations with the crucial aim of curtailing accidents and injuries to workers. It plays a crucial role in an organization aiming to achieve an anticipated outcome. A plethora of studies have found positive association between safety culture and safety performance of organizations. However, little is known on how the mechanism through which organizational safety culture exerts its influence on safety performance. Thus, this study investigates the indirect effect of safety management system in the relationship between organizational safety culture and safety performance. Methods: This study employs the use of a 5-point Likert questionnaire to collect data from 134 respondents who are head of safety officers in F&B industries located in Lagos, Nigeria. SmartPLS 2.0 was used for data analysis. Results: Results from path analysis revealed that safety culture and safety management system positively relate to safety performance. Furthermore, the mediation analysis indicated an indirect effect of safety management system in the relationship between safety culture and safety performance. Conclusion: It is concluded that though safety culture has a significant positive relationship on safety performance, however its effect will be more if F&B organizations create and constantly implement a robust safety management system.